Further notes on the development of the Serere (Uganda) herd of Shorthorned Zebu cattle - Wilson, P.N. (1957)
Performance of Shorthorned zebu cattle kept under different conditions of livestock management at Serere in Uganda were exaamined. Data on live weight gains, calf birth weights, calving rate, calf mortality and colour distribution included.